Working online or offline during COVID-19: Which has more impacts on stock price? - Jia, Wanjiao; Xu, Yuanyuan; Lu, Xiaowu (Frontiers in Psychology, 2022)
Remote work has become increasingly popular and important after the spread of COVID-19, but its impact on the financial market is in dispute. Using a unique dataset of analyst visits in China, we examine the impact of remote work on the financial market by comparing the market reaction of analysts’ online and offline visits. Results show that online visits have a significantly greater impact on stock prices than offline visits as discussion depth, information sharing, and information dissemination are enhanced. Additionally, online visits can predict the changes in funds’ holdings and firms’ future performance. Overall, our findings suggest that remote work improves the information environment of financial market during the COVID-19.